Femtosecond wavepacket dynamics reveals the molecular structures in the excited (S₁) and cationic (D₀) states - Kim, Junggil (2022)
Molecular structures in the electronically excited (S1) and cationic (D0) states of 2-fluorothioanisole (2-FTA) have been precisely refined from the real-time dynamics of the femtosecond (fs) wavepacket prepared by the coherent excitation of the Franck-Condon active out-of-plane torsional modes in the S1 ← S0 transition at 285 nm. The simulation to reproduce the experiment in terms of the beating frequencies gives the nonplanar geometry of 2-FTA in S1, where the out-of-plane dihedral angle (φ) of the S-CH3 moiety is 51° with respect to the molecular plane. The behavior of the fs wavepacket in terms of the amplitudes and phases with the change of the probe (ionization) wavelength (λprobe = 300-330 nm) provides the otherwise veiled structure of the cationic D0 state. While the 2-FTA cation adopts the planar geometry (φ = 0°) at the global minimum, it is found to have a vertical minimum at φ ≈ 135° from the perspective of the D0 ← S1 vertical transition. Ab initio calculations support the experiment quite well although the simulation using the model potentials could improve the match with the experiment, giving the new interpretation for the previously disputed photoelectron spectroscopic results.